PENGARUH PENGGUNAAN MAPLE SEBAGAI MEDIA PEMBELAJARAN PADA MATA KULIAH KALKULUS LANJUT - Arie Wahyuni (Universitas Muhammadiyah Semarang, 2018)
Further calculus is a compulsory subject that must be taken by mathematics education students, while many students are not interested in this course. This greatly affects the learning process of advanced calculus courses, so the lecturer changes the strategy so that students have an interest in learning advanced calculus. In the learning process the lecturer uses Maple learning media so that in learning students have enthusiasm for further calculus. The purpose of this study is as follows: 1) to determine the effect of student interest on Maple learning media on learning outcomes, especially on integral topics; 2) how much influencebetween student interest and Maple learning media on learning outcomes, especially on integral topics. The method used is experiment with linear regression analysis. The results showed that: (1) there was an influence between student interest and Maple learning media on learning outcomes, especially on integral topics, (2) the influence between student interest and Maple learning media on learning outcomes, especially on integral subject of 30,3%. Keywords: Influence, Maple, Advanced Calculus